The Effect of Agility and Balance Training on Dribbling Speed in Soccer Games (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
In terms of dribbling speed, the players are still not fast enough in dribbling. Objectives: (1) a more effective agility training method between zig-zag run and t-drill in increasing dribbling speed, (2) differences in the effect of high and low balance on increasing dribbling speed, (3) interaction between training methods agility with balance against increasing dribbling speed. This study uses an experimental method with a 2x2 factorial design. The independent variables in this study were zig-zag run and t-drill, high and low balance attribute variables, and the dependent variable was dribbling speed. The population is 40 players. The sampling technique used purposive sampling totaling 32 players. Data from the last test were analyzed with two-way ANOVA statistics. The results of calculations using SPSS 25 are obtained: 1) The first hypothesis is obtained Fcount > Ftable or 86.532 > 3.33 and a significance value of 0.000 <0.05. 2) The second hypothesis is obtained Fcount > Ftable or 77.184 > 3.33, and a significance value of 0.000 <0.05. 3) The third hypothesis is obtained by Fcount > Ftable or 9.615 > 3.33, and a significance value of 0.004 < 0.05. Conclusion: the group treated with the zig-zag run agility training method was better than the t-drill agility training group on dribbling speed. the group that has high balance is better than the group with low balance on the speed of dribbling. There is an interaction between agility training and the level of balance on the speed of dribbling.